MEDIA PUZZLE UNTUK KETERAMPILAN MENULIS SISWA KELAS X BAHASA 1 SMAN 1 GEDANGAN DALAM PEMBELAJARAN BAHASA JERMAN - LEMUNG, MARSELINA; IMAM SAMSUL, SUWARNO (LATERNE, 2018)
PUZZLE MEDIA FOR SKILLS WRITING STUDENT CLASS X SMAN 1 GEDANGAN IN GERMAN LEARNING Marselina Lemung German Language Education, Faculty of Language and Art, State University of Surabaya, Marselina_lemung@yahoo.co.id Drs. Suwarno Imam Samsul, M.pd German Language Education, Faculty of Language and Art, State University of Surabaya, Abstract Writing is an activity that people do to produce a writing. A good writing has its distinctly meaningful diantarannya is a one-unit, short and dense and meet the rules of language. Writing can be considered easy when one often practiced writing and can be considered difficult when a new person plunge or practice writing so do not know what to start from. This study uses simple sentences. A simple sentence is a sentence that has a subject element, predicate, and object. At the time of learning to write simple sentences many students have difficulty. The difficulty is caused by several factors namely lack of writing exercise, lack of vocabulary mastery, and ignorance of the meaning of the vocabulary. Therefore one of the learning media used to overcome this is using the media puzzle. The formulation of the problem in this research is